(untitled) (Baghdad Science Journal, 2024)
The investigation’s objective is to develop a new spectrophotometric method for determining methyldopa in both pure and pharmaceutical forms. The proposed process produces a colorful product by combining methyldopa with anisidine in the presence of potassium nitroprusside and sodium hydroxide. The effects of several factors on reaction yield were investigated, including the reagent concentration, reaction time and color stability period and the settings were optimized. The absorbance at 597 nm of the colored product was monitored spectrophotometrically. In concentration ranges of 0.50 to 80.0 µg. mL-1 the plots were linear, sandell’s sensitivity was 0.0218μg∙cm-1, the correlation coefficient was found to be (r = 0.9992). The detection limit was 0.0353μg∙ml-1, and the limit of quantitation was 0.2691μg∙ml-1. The reaction ratio between methyldopa and anisidine was studied and found to be 1:1. The proposed approach was validated and results obtained for the assay of three different brands of methyldopa tablets were compared with the BP method.